A kind of semi-absorbent cotton quilt core capable of being washed

By modifying semi-spotted cotton fibers, combining ester-containing polymers and nanometal oxides, the problems of warmth and cleanliness of the cotton quilt core after washing are solved, and efficient washing effect and antibacterial properties are achieved.

CN118749809BActive Publication Date: 2024-12-27NINGBO BOYANG HOME TEXTILE GRP CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411244317.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-06
Publication Date
2024-12-27
Estimated Expiration
2044-09-06

AI Technical Summary

Technical Problem

The cotton quilt core loses its warmth after washing or dry cleaning, and it is difficult to clean, so it is difficult for the prior art to have both warmth and washing effects.

Method used

Modified semi-spotted cotton fibers are used to fix the ester-containing polymer with nanometal oxides and fixed on the hydrogel, thereby improving the hydrophobicity and antibacteriality of the fibers, and reducing the cross-linking of the hydrogel with the cotton fibers. The occurrence of fiber agglomeration during cleaning.

Benefits of technology

The cotton quilt core is maintained with warmth and fluffy after washing, simplifying the cleaning process and enhancing antibacterial properties.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The invention discloses a washable semi-degreased cotton quilt core, comprising a quilt core cover and a cotton inner core filled in the quilt core cover; the cotton inner core is obtained by opening, blending and finishing modified semi-degreased cotton; the raw materials of the modified semi-degreased cotton include cotton fiber, modified hydrogel and loaded polymer; the raw materials of the modified hydrogel include polyhydroxyethyl methacrylate and a siloxane crosslinking agent; the loaded polymer includes an ester-containing polymer and a nano-metal oxide for fixing the ester-containing polymer; the synthesis of the modified semi-degreased cotton includes the following steps: preparation of modified hydrogel, synthesis of loaded polymer, loading of hydrogel and modification of semi-degreased cotton. The invention not only has a warming effect and fits human skin, but also has a water-washing effect, which is helpful for cleaning the cotton quilt core.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of cotton wool textiles, in particular to a semi-degreased cotton quilt core that can be washed. Background Art

[0002] Cotton is one of the most important natural fibers. It is abundant and often used in the production of clothing, household and medical supplies. However, since cotton fabrics contain many hydroxyl groups in their structure, cellulose is easy to absorb water and oil, and its anti-fouling performance is not ideal, which leads to the fact that cotton cannot be washed or dry-cleaned. If cotton is washed, it will lose its original warmth retention and will form clumps of hard cotton. Cotton after dry cleaning is even worse, the smell cannot be removed, and it will shrink into a ball. Nowadays, the only way to clean the core of a natural cotton quilt is to wash and remove the quilt cover, and the cotton inside can only be slowly dried in the sun, and then the surface is gently hit with a wooden stick to make the cotton quilt fluffy.

[0003] At present, cotton is degreased and chemically treated to remove the associated impurities. The associated impurities are mainly divided into two categories: one is polysaccharides and their derivatives, such as polypentose, polyhexose, pectin and starch; the other is non-sugar substances, such as lignin, resin or oil, wax, protein, inorganic salts and a small amount of tannin, pigment, etc. By degreasing cotton, the thermal insulation of defatted cotton is stronger and more suitable for close contact with human skin. Similarly, defatted cotton is easier to absorb liquid than ordinary cotton, and is often used in medical cotton and other fields.

[0004] Since cotton fabrics contain many hydroxyl groups in their structure, cotton fibers easily absorb water and oil, making their anti-fouling performance less than ideal. At present, in order to make cotton quilts have a water-washing effect, cotton fibers are often modified to increase the hydrophobicity of their surfaces. However, with the addition of hydrophobic structures, the thermal insulation effect of cotton fibers is much worse than before. In order to make the quilt core made of cotton warmer and closer to human skin, and at the same time have a water-washing effect, which is helpful for cleaning the cotton quilt core, the present application provides a solution. Summary of the invention

[0005] The present application provides a washable semi-degreased cotton quilt core, which not only has a warming effect and fits well to human skin, but also has a washable effect, which helps to clean the cotton quilt core.

[0006] The present application provides a washable semi-degreased cotton quilt core, comprising a quilt core cover and a cotton core filled in the quilt core cover; the cotton core is obtained by opening, blending and finishing modified semi-degreased cotton; the raw materials of the modified semi-degreased cotton include cotton fiber, modified hydrogel and loaded polymer; the raw materials of the modified hydrogel include polyhydroxyethyl methacrylate and silicone crosslinking agent; the loaded polymer includes an ester-containing polymer and a nano-metal oxide fixing the ester-containing polymer; the synthesis of the modified semi-degreased cotton includes the following steps: preparation of modified hydrogel, synthesis of loaded polymer, loading of hydrogel and modification treatment of semi-degreased cotton.

[0007] By adopting the above-mentioned technical scheme, the present application adopts the method of modifying semi-degreased cotton fibers with hydrophobic ester-containing polymers so that the surface of the cotton fibers has a hydrophobic effect; further, the ester-containing polymers are fixed on the nano-metal oxide, which helps to reduce the cross-linking reaction between the ester-containing polymers and the hydrogel, thereby improving the purity of the hydrogel during the preparation stage; in addition, since the hydrogel material has good biocompatibility and strong hydrophilicity, it can swell and retain a large amount of water molecules, and the cross-linking between the hydrogel material and the cotton fibers can reduce the occurrence of hard lumps of semi-degreased cotton during the cleaning process, thereby facilitating the cleaning of the quilt core.

[0008] Preferably, the ester-containing polymer includes one or more of polyethylene terephthalate, polycaprolactone, polyurethane, polycarbonate, and polybutyl acrylate.

[0009] Preferably, the nano metal oxide includes nano zinc oxide, nano iron oxide, and nano magnesium oxide.

[0010] By adopting the above technical scheme, the ester-containing polymer has a certain hydrophobic effect and can modify the surface of the cotton fiber. However, due to the low hydrophilicity of the ester-containing polymer, it is loaded on the nano metal oxide. Because the nano metal oxide has the characteristics of large specific surface area, small crystal grain and high surface energy, a large amount of oxygen vacancies are formed on the surface of the nano metal oxide, and the oxygen vacancies are used to fix the carbonyl position in the ester-containing polymer, so that the two are fixed. Further, the uniformity of the ester-containing polymer can be improved in the solution of the reactant at the nano metal oxide. In addition, the antibacterial effect of the nano metal oxide on cotton is also greatly improved.

[0011] Preferably, the preparation of the modified hydrogel comprises the following steps: preparation of polyhydroxyethyl methacrylate, synthesis of a silicone crosslinking agent and synthesis of the modified hydrogel.

[0012] Preferably, in the preparation process of the poly(hydroxyethyl methacrylate): hydroxyethyl methacrylate and azobisisobutyronitrile are dissolved in ethylene glycol monomethyl ether in a certain proportion for low-temperature reaction, and the system is kept closed, heated to 60°C-80°C for 4-8h, and after cooling to room temperature, rinsed with a mixed solution of n-hexane and methyl tert-butyl ether, and dried in a vacuum oven until the solvent evaporates to obtain poly(hydroxyethyl methacrylate).

[0013] Preferably, in the synthesis process of the silicon-oxygen crosslinking agent: 1,8-diamino-3,6-dioxaoctane is dissolved in dichloromethane, and 3-isocyanatepropyltrimethoxysilane is slowly added in a certain proportion, reacting at low temperature for 2-5 hours, and rotary evaporating the solvent at room temperature, and then washing with petroleum ether 3-5 times and drying to obtain the silicon-oxygen crosslinking agent.

[0014] Preferably, in the synthesis process of the modified hydrogel: poly(hydroxyethyl methacrylate) and a silicone crosslinking agent are stirred and dissolved in a certain proportion at room temperature, and a certain amount of 1,5,9-triazacyclododecane is added and stirred to react for 12-24 hours to obtain a modified hydrogel (dynamically crosslinked poly(hydroxyethyl methacrylate) hydrogel).

[0015] By adopting the above technical scheme, firstly, free radicals on hydroxyethyl methacrylate are polymerized to obtain polyhydroxyethyl methacrylate, wherein the polyhydroxyethyl methacrylate has preliminary hydrogel properties, thereby having a physical support effect on cotton fibers, reducing the damage to the cotton fibers, and increasing their thermal insulation effect.

[0016] Secondly, the present application utilizes the high reactivity between isocyanate and amino to synthesize a hexafunctional silane coupling agent containing a flexible ether bond as a cross-linking agent for removing small molecules from poly(hydroxyethyl methacrylate) hydrogel. Finally, the above two are mixed to allow dynamic covalent bond exchange between the silane bond and the hydroxyl group of the siloxane cross-linking agent molecule, thereby enabling the prepared modified hydrogel to improve the electrical stability of the nano-metal oxide in the hydrogel, thereby facilitating the fixation of the loaded polymer on the hydrogel, and facilitating the storage of the loaded polymer and the modified hydrogel together, thereby facilitating the modification of semi-defatted cotton.

[0017] Preferably, the synthesis of the loaded polymer comprises the following steps: mixing N,N-dimethylformamide and dichloromethane in a certain proportion, heating to dissolve the ester-containing polymer, stirring for 12-24 hours, thereby obtaining a mixed solution containing the ester-containing polymer, and then continuing to add a certain proportion of nano-metal oxides to the mixed solution containing the ester-containing polymer and performing ultrasonic treatment for 2-6 hours to ensure that the nano-metal oxide particles are uniformly dispersed in the solution, and then drying after rotary evaporation of the solvent to obtain the loaded polymer.

[0018] Preferably, the loading of the hydrogel comprises the following steps: dissolving the modified hydrogel in anhydrous DMF in a certain proportion, heating to 80°C-100°C, adding the loaded polymer and stirring the reaction for 12h-24h, cooling to room temperature after the reaction, extracting with dichloromethane and methanol, fixing the loaded polymer on the modified hydrogel, and storing it in an environment of 20°C-50°C.

[0019] Preferably, the modification treatment of the semi-degreased cotton includes the following steps: placing the cotton in a high-temperature drying machine and adjusting the temperature to 80°C-90°C for 3h-6h to perform a semi-degreasing operation on the cotton; dissolving the modified hydrogel with a load in a 50% ethanol solution, and dissolving a certain proportion of semi-degreased cotton fibers in the mixed solution, stirring at 40°C-60°C for 2h-5h, then adding a certain amount of potassium carbonate, maintaining the temperature at 60°C-80°C for 1h-3h, and then filtering and drying to achieve surface modification of the semi-degreased cotton; opening and combing the modified cotton fibers to make a mesh cotton layer, and stacking the mesh cotton layers layer by layer to make a cotton base, and then using a cotton kneading machine to knead the base to make a cotton inner core.

[0020] By adopting the above technical scheme, the cotton of the present application adopts the means of heating degreasing to remove the fat and wax on the surface of the cotton, so that part of the hydroxyl groups on the cotton fibers are exposed for reacting with the ester-containing polymer to achieve modification of the cotton fibers; the remaining part of the cotton fibers is physically cross-linked with the hydrogel due to the network structure therein, so that the cotton fibers have a certain physical support, reducing the damage of the cotton fibers, and thus increasing their thermal insulation effect.

[0021] Furthermore, the modified hydrogel with the load is dissolved in an ethanol solution, and the semi-defatted cotton fiber is dissolved in the mixed solution, so that the surface of the cotton fiber can be evenly contacted with the mixed solution. The cotton fiber is physically cross-linked with the hydrogel due to the network structure therein. At the same time, during the temperature control process, the ester-containing polymer will carry the nano-metal oxide to react with the hydroxyl group on the surface of the cotton fiber. The present application adopts a two-step method, in which the load polymer and the modified hydrogel are stored together, and reacted together with the semi-defatted cotton, which facilitates the modification of the semi-defatted cotton.

[0022] One or more technical solutions provided in this application have at least the following technical effects or advantages:

[0023] 1. The present application adopts the method of modifying semi-degreased cotton fiber with a hydrophobic ester-containing polymer so that the surface of the cotton fiber has a hydrophobic effect.

[0024] 2. The present application adopts the method of fixing the ester-containing polymer on the nano-metal oxide, which helps to reduce the cross-linking reaction between the ester-containing polymer and the hydrogel and improve the purity of the modified hydrogel and the loaded polymer during the preparation stage.

[0025] 3. The present application adopts hydrogel to cross-link cotton fibers. The hydrogel material can swell and retain a large amount of water molecules, thereby reducing the occurrence of hard lumps of semi-defatted cotton during the cleaning process, thereby facilitating the cleaning of the quilt core. DETAILED DESCRIPTION

[0026] The present application provides a washable semi-degreased cotton quilt core, which not only has a warming effect and fits well to human skin, but also has a washable effect, which helps to clean the cotton quilt core.

[0027] The technical solutions in the embodiments of the present application are described clearly and completely below. Obviously, the described embodiments are only a part of the embodiments of the present application, rather than all the embodiments. Based on the embodiments in the present application, all other embodiments obtained by ordinary technicians in the field without creative work are within the scope of protection of the present application.

[0028] It should be noted that the terms "including" and "having" and any variations thereof in the specification and claims of the present application are intended to cover non-exclusive inclusions. For example, a process, method, system, product or server that includes a series of steps or units is not necessarily limited to those steps or units explicitly listed, but may include other steps or modules that are not explicitly listed or are inherent to these processes, methods, products or devices.

[0029] raw material

[0030] Cotton: The cotton used in the examples of the present application is commercially available Sea Island cotton, also known as Xinjiang long-staple cotton, with 3 to 5 half-cleft leaves, 5 epicalyxes, and shallowly lobed edges into sharp teeth. It is long-fiber, fine-staple cotton.

[0031] The following raw materials are all commercially available chemical products, and the CAS numbers and other parameters of the raw materials are listed below.

[0032] Hydroxyethyl methacrylate CAS No.: 868-77-9 Molecular weight: 130.14 Purity: 99.5%;

[0033] Azobisisobutyronitrile CAS number: 78-67-1 Molecular weight: 164.208 Purity: 99.5%;

[0034] Ethylene glycol monomethyl ether CAS number: 109-86-4 Molecular weight: 76.094 Purity: 99.5%;

[0035] n-Hexane CAS No.: 110-54-3 Molecular weight: 86.175 Purity: 99.5%;

[0036] Methyl tert-butyl ether CAS number: 1634-04-4 Molecular weight: 88.148 Purity: 99.5%;

[0037] 1,8-Diamino-3,6-dioxaoctane CAS No.: 929-59-9 Molecular weight: 148.203 Purity: 99.5%;

[0038] 3-Isocyanatepropyltrimethoxysilane CAS No.: 15396-00-6 Molecular weight: 189.284 Purity: 99.5%;

[0039] Petroleum ether CAS number: 8030-30-6 Molecular weight: N / A Purity: 99.0%;

[0040] 1,5,9-Triazacyclododecane CAS No.: 294-80-4 Molecular weight: 171.283 Purity: 99.5%;

[0041] N,N-Dimethylformamide CAS number: 68-12-2 Molecular weight: 73.094 Purity: 99.8%;

[0042] Dichloromethane CAS number: 75-09-2 Molecular weight: 84.933 Purity: 99.5%;

[0043] Methanol CAS No.: 67-56-1 Molecular weight: 32.042 Purity: 99.5%;

[0044] Potassium carbonate CAS number: 584-08-7 Molecular weight: 138.21 Purity: 99.5%;

[0045] Polyethylene terephthalate CAS No.: 25038-59-9 Molecular weight: N / A Purity: 99.5%;

[0046] Polycaprolactone CAS No.: 24980-41-4 Molecular weight: 114.142 Purity: 99.5%;

[0047] Polyurethane CAS No.: 30322-28-2 Molecular weight: N / A Purity: 99.5%;

[0048] Polycarbonate CAS No.: 25766-59-0 Molecular weight: N / A Purity: 99.5%;

[0049] Polybutyl acrylate CAS No.: 9003-49-0 Molecular weight: 128.169 Purity: 99.5%;

[0050] Nano zinc oxide CAS number: 1314-13-2 Molecular weight: 81.390 Purity: 99.5%;

[0051] Nano-iron oxide CAS number: 1332-37-2 Molecular weight: 71.844 Purity: 99.5%;

[0052] Nano magnesium oxide CAS number: 1309-48-4 Molecular weight: 40.304 Purity: 99.5%.

[0053] Example 1

[0054] S1. Preparation of modified hydrogel:

[0055] 1. Preparation of poly(hydroxyethyl methacrylate): 50 g of hydroxyethyl methacrylate and 0.8 g of azobisisobutyronitrile were dissolved in 500 ml of ethylene glycol monomethyl ether for low-temperature reaction. The temperature was controlled below 5°C for 1 hour. In the process of maintaining a closed system, the reaction was heated to 70°C for 8 hours. After cooling to room temperature, the reaction was rinsed 3 times with a 1:1 mixed solution of n-hexane and methyl tert-butyl ether, and dried in a vacuum oven for 24 hours until the solvent evaporated to obtain poly(hydroxyethyl methacrylate).

[0056] 2. Synthesis of siloxane crosslinking agent: Dissolve 30 g of 1,8-diamino-3,6-dioxaoctane in 500 ml of dichloromethane, and slowly add 100 g of 3-isocyanatepropyltrimethoxysilane, react in an ice-water mixed bath for 5 h, and rotary evaporate the solvent at room temperature. Then wash with petroleum ether three times and dry in a vacuum oven for 24 h to obtain a siloxane crosslinking agent.

[0057] 3. Synthesis of modified hydrogel: Take 40 g of the above-obtained poly(hydroxyethyl methacrylate) and 10 g of a silicone crosslinking agent and stir to dissolve at room temperature, add 3 g of 1,5,9-triazacyclododecane and stir to react for 24 h, and maintain at 80 ° C and reverse vacuum for 2 h to obtain a modified hydrogel (dynamically cross-linked poly(hydroxyethyl methacrylate) hydrogel).

[0058] S2. Synthesis of supported polymer:

[0059] 30 g of N,N-dimethylformamide was mixed with 70 g of dichloromethane, and the temperature was raised to 80°C, and 20 g of polycaprolactone was added and stirred for 24 hours to obtain a mixed solution with polycaprolactone. Then, 10 g of nano zinc oxide particles were added to the mixed solution with polycaprolactone and ultrasonic treatment was performed for 6 hours to ensure that the nano zinc oxide particles were evenly dispersed in the solution. After the solvent was rotary evaporated, it was dried in a vacuum oven for 24 hours to obtain a loaded polymer (loaded polymer of polycaprolactone and nano zinc oxide).

[0060] S3. Hydrogel loading:

[0061] The 20 g modified hydrogel prepared above was dissolved in 100 ml of anhydrous N,N-dimethylformamide and heated to 80°C, then the loaded polymer (loaded polymer of polycaprolactone and nano zinc oxide) was added and stirred for reaction for 24 hours. After the reaction was completed, the temperature was cooled to room temperature, and then extracted with dichloromethane and methanol to fix the loaded polymer on the modified hydrogel and store it in an environment of 30°C.

[0062] S4. Modification of semi-degreased cotton:

[0063] The cotton was placed in a high-temperature dryer and the temperature was adjusted to 80°C for 6 hours to perform a semi-degreasing operation on the cotton; 30g of the modified hydrogel with a loaded polymer was dissolved in a 50% ethanol solution, and 400g of the semi-degreased cotton fiber was dissolved in the mixed solution, stirred at 50°C for 4 hours, and then 1.2g of potassium carbonate was added, and the temperature was maintained at 60°C for 3 hours, and then filtered and dried to achieve surface modification of the semi-degreased cotton; the modified cotton fibers were opened and combed to make a mesh cotton layer, and the mesh cotton layers were stacked layer by layer to make a cotton base, and then a cotton kneading machine was used to knead the base to make a cotton inner core.

[0064] Example 2

[0065] The difference between Example 2 and Example 1 is that the ester-containing polymer is polyethylene terephthalate, and the loaded polymer is prepared by using polyethylene terephthalate as the modification of cotton fiber.

[0066] Example 3

[0067] The difference between Example 3 and Example 1 is that the ester-containing polymer is polyurethane, and the loaded polymer is prepared by polyurethane to modify the cotton fiber.

[0068] Example 4

[0069] The difference between Example 4 and Example 1 is that the ester-containing polymer is polycarbonate, and the loaded polymer is prepared by using polycarbonate to modify the cotton fiber.

[0070] Example 5

[0071] The difference between Example 5 and Example 1 is that the ester-containing polymer is polybutyl acrylate, and the loaded polymer is prepared by using polybutyl acrylate to modify the cotton fiber.

[0072] Comparative Example 1

[0073] The difference between Comparative Example 1 and Example 1 is that, during the modification process of the semi-degreased cotton, polycaprolactone and the semi-degreased cotton fibers are dissolved in a 50% ethanol solution.

[0074] Comparative Example 2

[0075] The difference between Comparative Example 2 and Example 1 is that, during the modification process of semi-degreased cotton, polycaprolactone and nano zinc oxide particles are reacted with each other, and the formed polycaprolactone and nano zinc oxide loaded polymer and semi-degreased cotton fibers are dissolved in a 50% ethanol solution.

[0076] Comparative Example 3

[0077] The difference between Comparative Example 3 and Example 1 is that the hydrogel made of polyhydroxyethyl methacrylate is dissolved in a 50% ethanol solution together with semi-defatted cotton fibers.

[0078] Comparative Example 4

[0079] The difference between Comparative Example 4 and Comparative Example 3 is that the hydrogel made of polyhydroxyethyl methacrylate is not modified by a silicone crosslinking agent, but is directly mixed with a load polymer for storage.

[0080] Performance testing

[0081] In order to further study the effects of various components and preparation parameters on the semi-defatted cotton quilt core, the present application further carries out the following examples for verification.

[0082] According to Examples 1-5 and Comparative Examples 1-4, the composite fiber cores prepared in each Example and each Comparative Example were tested for thermal insulation performance, heat transfer performance, and fluffiness after washing. The composite fiber cores were washed according to the method in GB / T8629-2017 "Household Washing and Drying Procedure for Textile Testing", with a washing degree of 5N, and washed 0, 20, 50, and 100 times, respectively. The washed composite fiber cores were dried and placed in an environment of 20°C and a relative humidity of 70% for 24 hours to test the thermal insulation performance, heat transfer performance, and fluffiness after washing.

[0083] 1. Thermal insulation performance test: The test is carried out in accordance with GB / T11048-2009 "Test method for thermal insulation performance of textiles". The flat plate constant temperature difference heat dissipation method is adopted to calculate the percentage of the difference between the heat dissipation when there is no sample and the heat dissipation when there is a sample and the ratio of the heat dissipation when there is no sample.

[0084] 2. Heat transfer performance test: GB / T35762-2017 "Textile Thermal Transfer Performance Test Method Flat Plate Method" is used for testing to obtain the heat transfer coefficient.

[0085] 3. Fluffiness test: According to AATCC 135-2004 "Dimensional changes of fabrics after home washing", the size ratio of the semi-degreased cotton quilt core is tested after multiple washings to obtain its fluffiness after multiple washings.

[0086] Table 1, Performance test table of Examples 1-5 and Comparative Examples 1-4

[0087]

[0088] 1. Thermal insulation performance test: the unit is H thermal insulation rate / %.

[0089] 2. Heat transfer performance test: the unit is U heat transfer coefficient / (w / m2*℃).

[0090] 3. Fluffiness test: The unit is the ratio of the size of the cotton quilt core of zero washing / %.

[0091] *During the fluffiness test, there is a certain degree of cotton agglomeration (volume>1000mm 3 )Appear.

[0092] Conclusion Analysis

[0093] According to the above test, the thermal insulation performance of the semi-degreased cotton quilt core is tested. Compared with Examples 1-5 and Comparative Example 1, in the modification process of the semi-degreased cotton, polycaprolactone and semi-degreased cotton fibers are modified, and the semi-degreased cotton is given a certain hydrophobicity by polycaprolactone, and its thermal insulation performance is poor. During multiple washing processes, the semi-degreased cotton quilt core will lose a certain thermal insulation effect. The heat transfer coefficient in the heat transfer performance refers to the heat transferred through a unit area under thermal stability conditions, so the stronger the heat transfer capacity, the worse the thermal insulation effect. Therefore, after multiple washing processes, the heat transfer coefficient of the semi-degreased cotton quilt core in Comparative Example 1 increases rapidly.

[0094] Compared with Comparative Example 2, in the modification process of semi-degreased cotton, polycaprolactone and nano zinc oxide particles are reacted with each other to form a loaded polymer of polycaprolactone and nano zinc oxide, and the semi-degreased cotton fiber is modified. Its thermal insulation performance does not change much, but its hydrophobic effect is increased, so that the size reduction rate of Comparative Example 2 is reduced after multiple washing processes compared with Comparative Example 1, and the fluffiness of the semi-degreased cotton quilt core is greater.

[0095] In addition, compared with Comparative Example 3, by making polyhydroxyethyl methacrylate into hydrogel, the hydrogel is fixed to the cotton fiber in the form of physical crosslinking, which can make the cotton fiber have certain thermal insulation performance. However, after a few washes, the fluffiness of the semi-defatted cotton quilt core can still reach a good state, and most of the water is absorbed by the hydrogel; the shrinkage of the semi-defatted cotton quilt core is acceptable. However, during multiple washes, the water absorption structure of the hydrogel reaches saturation, resulting in the phenomenon of agglomeration of the cotton fibers, which in turn causes the fluffiness in Comparative Example 3 to begin to decrease.

[0096] In addition, compared with Examples 1-5 and Comparative Example 3, in Comparative Example 4, the hydrogel made of polyhydroxyethyl methacrylate was not modified with a silicone crosslinking agent, but was directly mixed with a load polymer for storage; which would result in stratification of the polyhydroxyethyl methacrylate hydrogel and the load polymer (load polymer of polycaprolactone and nano zinc oxide) during the storage process, and in the modification process of the semi-degreased cotton, the load polymer did not fully react with the hydroxyl groups on the cotton fibers, thereby reducing the hydrophobicity of the semi-degreased cotton, causing the fluffiness of the semi-degreased cotton quilt core to decrease after multiple washings.

[0097] In addition, compared with the analysis of Examples 1-5, since polycaprolactone has fewer side chains and more excellent structural advantages, it has a certain hydrophobic effect when reacting with cotton fibers. At the same time, due to its skeleton structure, the warmth retention effect of the semi-defatted cotton quilt core also has certain advantages. Therefore, Example 1 is the best example among Examples 1-5.

[0098] Embodiment 6-7

[0099] Example 6

[0100] The difference between Example 6 and Example 1 is that during the synthesis of the supported polymer, the nano metal oxide is nano iron oxide.

[0101] Example 7

[0102] Example 7 is different from Example 1 in that, during the synthesis of the supported polymer, the nano metal oxide is nano magnesium oxide.

[0103] Performance testing

[0104] In order to further study the effects of various components and preparation parameters on the semi-defatted cotton quilt core, the present application further carries out the verification of the above-mentioned consistent embodiments.

[0105] Table 2, Performance test table of Examples 1, 6-7

[0106]

[0107] According to the above test analysis, for the thermal insulation performance test of the semi-defatted cotton quilt core, compared with Example 1, the difference of the nano metal oxide on the thermal insulation performance, heat transfer performance and fluffiness of the cotton quilt core in Examples 6-7 is not very large. The thermal insulation performance and heat transfer performance of Example 1 are slightly worse than those of Example 6.

[0108] Therefore, this application tests the antibacterial properties of different nano-metal oxides. This embodiment 1 and embodiments 6-7 are tested in accordance with GB / T20944.3-2008 "Evaluation of antibacterial properties of textiles Part 3: Oscillation method". Among them, the antibacterial test strains are Escherichia coli, Candida albicans and Staphylococcus aureus.

[0109] Table 3, Performance test table of Examples 1, 6-7

[0110]

[0111] The antibacterial effects of Example 1 and Examples 6-7 are analyzed. In the present application, the nano metal oxide in Example 1 is nano zinc oxide, which has a better antibacterial effect, but the warmth retention and heat transfer performance are slightly worse than those in Example 6. In order to make people have a better experience in using the semi-defatted cotton quilt core. In the present application, Example 1 is the best example.

[0112] It should be noted that the above-mentioned sequence of the embodiments of the present application is only for description and does not represent the advantages and disadvantages of the embodiments. And the above-mentioned specific embodiments of this specification are described. Other embodiments are within the scope of the attached claims. In some cases, the actions or steps recorded in the claims can be performed in an order different from that in the embodiments and still achieve the desired results. In some embodiments, multitasking and parallel processing are also possible or may be advantageous.

[0113] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present application should be included in the protection scope of the present application.

[0114] This specification is merely an exemplary description of the present application and is deemed to have covered any and all modifications, variations, combinations or equivalents within the scope of the present application. Obviously, those skilled in the art may make various modifications and variations to the present application without departing from the scope of the present application. Thus, if these modifications and variations of the present application fall within the scope of the present application and its equivalents, the present application is intended to include these modifications and variations.

Claims

1. A washable semi-absorbent cotton quilt core, characterized in that: The invention comprises a quilt core cover and a cotton core filled in the quilt core cover; the cotton core is obtained by opening, blending and finishing modified semi-degreased cotton; the raw materials of the modified semi-degreased cotton include cotton fiber, modified hydrogel and loaded polymer; the raw materials of the modified hydrogel include polyhydroxyethyl methacrylate and a silicone crosslinking agent; the loaded polymer includes an ester-containing polymer and a nano-metal oxide fixing the ester-containing polymer; the synthesis of the modified semi-degreased cotton includes the following steps: preparation of the modified hydrogel, synthesis of the loaded polymer, loading of the hydrogel and modification of the semi-degreased cotton; The preparation of the modified hydrogel comprises the following steps: preparation of polyhydroxyethyl methacrylate, synthesis of a silicone crosslinking agent and synthesis of the modified hydrogel; In the preparation process of poly(hydroxyethyl methacrylate), hydroxyethyl methacrylate and azobisisobutyronitrile are dissolved in ethylene glycol monomethyl ether in a certain proportion for low-temperature reaction, and the system is kept closed, heated to 60° C.-80° C. for 4-8 hours, and after cooling to room temperature, rinsed with a mixed solution of n-hexane and methyl tert-butyl ether, and dried in a vacuum oven until the solvent evaporates to obtain poly(hydroxyethyl methacrylate); In the synthesis process of the silicon-oxygen crosslinking agent: 1,8-diamino-3,6-dioxaoctane is dissolved in dichloromethane, and 3-isocyanatepropyltrimethoxysilane is slowly added in a certain proportion, reacting at low temperature for 2-5 hours, and rotary evaporating the solvent at room temperature, and then washing with petroleum ether for 3-5 times and drying to obtain the silicon-oxygen crosslinking agent; In the synthesis process of the modified hydrogel: polyhydroxyethyl methacrylate and a silicone crosslinking agent are stirred and dissolved at room temperature in a certain proportion, and a certain amount of 1,5,9-triazacyclododecane is added and stirred to react for 12-24 hours to obtain the modified hydrogel.

2. The washable semi-degreased cotton quilt core according to claim 1, characterized in that: The ester-containing polymer includes one or more of polyethylene terephthalate, polycaprolactone, polyurethane, polycarbonate, and polybutyl acrylate.

3. The washable semi-degreased cotton quilt core according to claim 2, characterized in that: The nano metal oxides include nano zinc oxide, nano iron oxide and nano magnesium oxide.

4. The washable semi-degreased cotton quilt core according to claim 1, characterized in that: The synthesis of the loaded polymer comprises the following steps: N,N-dimethylformamide and dichloromethane are mixed in a certain proportion, and the temperature is increased to dissolve the ester-containing polymer, and stirred for 12-24 hours to obtain a mixed solution containing the ester-containing polymer. Then, a certain proportion of nano-metal oxides are added to the mixed solution containing the ester polymer and ultrasonic treatment is performed for 2-6 hours to ensure that the nano-metal oxide particles are uniformly dispersed in the solution. After the solvent is rotary evaporated, it is dried to obtain a loaded polymer.

5. The washable semi-degreased cotton quilt core according to claim 4, characterized in that: The loading of the hydrogel comprises the following steps: The modified hydrogel is dissolved in anhydrous N,N-dimethylformamide in a certain proportion, and after heating to 80°C-100°C, the loaded polymer is added and stirred to react for 12h-24h. After the reaction is completed, the temperature is cooled to room temperature, and then extracted with dichloromethane and methanol to fix the loaded polymer on the modified hydrogel and store it in an environment of 20°C-50°C.

6. The washable semi-degreased cotton quilt core according to claim 5, characterized in that: The modification process of the semi-degreased cotton comprises the following steps: The cotton is placed in a high-temperature dryer and the temperature is adjusted to 80°C-90°C for 3h-6h to perform a semi-degreasing operation on the cotton; the modified hydrogel with a loaded polymer is dissolved in a 50% ethanol solution, and a certain proportion of semi-degreased cotton fibers are dissolved in the mixed solution, stirred at 40°C-60°C for 2h-5h, and then a certain amount of potassium carbonate is added, and the temperature is maintained at 60°C-80°C for 1h-3h, and then filtered and dried to achieve surface modification of the semi-degreased cotton; the modified cotton fibers are opened and combed to form a mesh cotton layer, and the mesh cotton layers are stacked layer by layer to form a cotton base, and then a cotton kneading machine is used to knead the base to form a cotton inner core.